A new species of freshwater mussel in the genus Popenaias Frierson, 1927, from the Gulf coastal rivers of central Mexico (Bivalvia: Unionida: Unionidae) with comments on the genus - Inoue, Kentaro; Cummings, Kevin S.; Tiemann, Jeremy S.; Miller, Thomas D.; Johnson, Nathan A.; Smith, Chase H.; Randklev, Charles R. (Zootaxa, 2020)
The Gulf coastal drainages of central Mexico are a faunal transition zone between North and South America and harbor a unique assemblage of freshwater mussels (Bivalvia: Unionida). However, little information is available regarding the taxonomy, distribution, and evolutionary history of the Mexican mussel fauna due to limited sampling over the last 100 years. To address these knowledge gaps, we evaluated species-level diversity in the genus Popenaias Frierson, 1927, in Mexican Gulf coastal drainages as part of a larger effort to inform conservation efforts for members of this genus both in Mexico and the United States of America. Based on our analyses, we describe Popenaias berezai n. sp. from the Río Valles of the Río Pánuco basin, San Luis Potosí, Mexico. We also provide presumptive distributional range, phylogenetic structure, and molecular and morphological diagnoses of the new species and provide comments on the other species currently in Popenaias. Our findings highlight the high levels of endemism among freshwater mussels in Mexican Gulf coastal drainages and will help guide impending conservation actions for P. popeii, which is listed as “endangered” in the United States.